ZAKAT PENANGGULANGAN PANDEMI COVID-19 DALAM PERSPEKTIF FILSAFAT HUKUM ISLAM - Lina Nur Anisa (Investama : Jurnal Ekonomi dan Bisnis, 2023)
Since the global Covid-19 pandemic broke out in Indonesia, people are living in difficult conditions so they need help, both in the form of material and financial support. Zakat is one of the social funds in Islam which has a strategic role in meeting these needs. The material studied in this research relates to efforts to metabolize zakat to combat the Covid-19 pandemic. The method used in this study was library research and data collection techniques were carried out by library research, using an Islamic legal philosophy approach, to arrive at the conclusion that zakat may be given to those affected by Covid-19, to medical personnel, corona patients or citizens with confirmed Covid-19 families, who have been dismissed for physical or social reasons distancing is a government policy to minimize transmission of Covid-19